Development of Student Worksheets (LKPD) Based on Scientific Literacy for the Ecosystem Learning Materials - Nurhalimah, Siti; Paujiah, Epa; Solikha, Maratus; Cahyanto, Tri; Hadiansah, Hadiansah (FKIP - Universitas Riau, 2025)
Scientific literacy is a crucial skill in modern education. However, the limited availability of effective learning media remains one of the main factors contributing to the low level of scientific literacy among students in Indonesia. This study aims to develop a scientific literacy-based Student Worksheet (LKPD) as a learning medium. The research employed a Research and Development (R&D) approach using the 3D model, which consists of Define, Design, and Develop stages. Data were collected and analyzed through interviews, validation sheets completed by material experts and media experts, readability assessments conducted by a biology teacher and students, and response questionnaires administered to fifteen 10th-grade students at MAN 1 Bandung. The data were interpreted using a Likert scale. The results indicated that the LKPD received a validation score of 72% (valid) from the material expert and 92% (highly valid) from the media expert. The readability test produced scores of 81.2% (easy to understand) from the teacher and 87.3% of students. Student responses were also highly positive, with an average score of 86.6%. Based on these findings, the developed LKPD is feasible for classroom use and engage students in practicing scientific literacy skills.